Mental Health Literacy or Medicalization? The Impact of Psychology Content on TikTok on Generation Z Self-Diagnosis - Ahmad Syamsul Muarif (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2026)
This integrative literature review examines whether psychology content on TikTok strengthens mental health literacy or promotes the medicalization of ordinary distress and self-diagnosis among Generation Z. Peer-reviewed publications from 2019 to July 2026 were traced through PubMed, Google Scholar, and publisher databases, supplemented by foundational literature on mental health literacy, medicalization, and media effects. Twenty-eight publications were analyzed thematically. The synthesis identifies a dual pathway. TikTok may increase access to psychological language, normalize help-seeking, reduce isolation, and connect young people with professional resources. Conversely, symptom checklists, decontextualized personal narratives, inaccurate information, and algorithmic repetition may encourage overidentification, self-labeling, health anxiety, and the interpretation of common emotional experiences as psychiatric disorders. Evidence does not support a simple deterministic conclusion: effects vary according to content quality, prior distress, digital health literacy, source credibility, and access to professional assessment. The article proposes an exposure–identification–algorithmic reinforcement–self-labeling–action model and recommends TikTok-informed assessment, nonjudgmental diagnostic clarification, and algorithmically informed mental health literacy in counseling and psychotherapy.